Meningkatkan Hasil Belajar Melalui Metode Information Search: Mengakomodasi Keragaman di Sekolah Dasar - Nurliani, Reni; Evanirosa; Gradini, Ega; Nurjani; Firmansyah B (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
This research aims to improve the learning outcomes of grade IV students of SDN 4 Karangpawitan on the material The Beauty of Mutual Respect in Diversity through the application of the Information Search learning method. This method encourages active involvement of students in searching, evaluating, and utilizing information effectively, based on constructivism theory, inquiry-based learning, and planned behavior theory. The research uses the Classroom Action Research (PTK) approach in two cycles involving 13 students. Data was collected through learning outcome tests, observations, and documentation. The results showed a significant increase in the second cycle, with the average student score reaching 85 and learning completion of 92%. Student activity in learning increased from 61% in the first cycle to 88% in the second cycle. The application of this method has succeeded in creating an interactive learning atmosphere, increasing student understanding, and supporting the formation of inclusive characters. This study proves the effectiveness of the Information Search method in thematic learning based on diversity values.